Application of simulation of needle puncture with banana model in the teaching of straight buttonhole technique (香蕉模拟穿刺模型在直行式扣眼穿刺教学中的应用) - ZHENG Juanlian (郑娟莲); LIANG Yanping (梁艳萍); GAO Lei (高蕾); ZHENG Yueying (郑月英); ZHANG Yu (张毓) (中西医结合护理)
Objective To explore the simulation of needle puncture with banana model in the teaching of straight buttonhole technique. Methods The banana model was used to replace the buttonhole of human arteriovenous fistula, 16G steel needle was used for escharectomy and 16G blunt needle was used for puncture. The clinical teaching and training efficacy was evaluated. Results There were 120 nurses attended the training of straight buttonhole technique. After the operation practice, 98. 33% of the nurses have reached the personal goal of this study, and the satisfaction of model demonstration was high(100. 00%). Conclusion Simulation of needle puncture with banana model can assist teaching effectively, help nurses understand the technical essentials, and get better teaching effect. (目的 探讨香蕉模拟穿刺模型应用于动静脉内瘘直行式扣眼穿刺教学中的应用效果。方法 以香蕉代替人体动静脉内瘘模拟扣眼穿刺对120名护士进行教学培训, 评价教学效果。结果 本组护士扣眼穿刺培训的课程评价得分为(53. 9±0. 81)分, 99. 17%的护士对本次教学练习的有效性给予了肯定, 98. 33%的护士认为达到了本次学习的个人目标, 本次动静脉内瘘扣眼穿刺教学的满意度为100. 00%。结论 香蕉模拟穿刺模型能够有效地辅助教学, 帮助护士理解技术要领, 获得较好的教学效果。)